Decentralized despotism? Indirect colonial rule undermines contemporary democratic attitudes - Marie Lechler; Lachlan McNamee (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2017)
This paper identifies indirect and direct colonial rule as causal factors in shaping support for democracy by exploiting a within-country natural experiment in Namibia. Throughout the colonial era, northern Namibia was indirectly ruled through a system of appointed indigenous traditional elites whereas colonial authorities directly ruled southern Namibia. This variation originally stems from where the progressive extension of direct German control was stopped after a rinderpest epidemic in the 1890s, and thus constitutes plausibly exogenous within-country variation in the form of colonial rule. Using this spatial discontinuity, we find that individuals in indirectly ruled areas are less likely to support democracy and turnout at elections. We explore potential mechanisms and find suggestive evidence that the greater influence of traditional leaders in indirectly ruled areas has socialized individuals to accept non-electoral bases of political authority.
urn:nbn:de:bvb:19-epub-36388-0
Keywords: F54; N27; N47; P16; 330; Indirect Colonial Rule; Decentralized Despotism; Political Attitudes; Namibia; Democratic Institutions; Spatial RDD